Legal Gaps in the Implementation of the Cyber Notary Concept Based on Indonesian Civil Law - Rizmi, Nurfadhilah; Syari, Irna Komala; Setianingrum, Wulan; Yusuf, Chandra (Program Studi Master of Notary Law (S2), Faculty of Law, Universitas Islam SUltan Agung, 2024)
Implementation Cyber Notary cannot be separated from the legal system that supports it. Indonesia still uses the legal systemCivil Lawwhich originated from the Dutch era, especially in civil law. Indonesia still usesBugerlijk Wetboek Voor Indonesia (BW) in 1848 which was translated into the Civil Code (KUH Per). KUH Per regulates perfect evidence as an authentic deed. This authentic deed is made based on the provisions in KUH Per. Then the lack of regulation regarding public officials which made it stated in Law Number: 2 of 2014 concerning Amendments to Law Number: 30 of 2004 concerning the Position of Notary (UUJN). The law states aboutCyber Notaryin his explanation. Further developments, the Indonesian government has not made implementing regulations. In this study, the author aims to discussthe need to develop the concept of notary into a broader conceptdraftCyber Notarywhat is meant in the explanation of Article 15 paragraph (3) UUJN is connected to the conceptInternational Union of Notaries(UINL) in 1994 in a Civil Law country. In the discussion, the importance of the conceptCyber Notaryis related to the application of the conceptCyber Notaryin Indonesia whichsupporting the goals of the ASEAN Economic Communityand AFTA. So far, Indonesia still follows the concept of authentic deeds regulated in the Civil Code, even though the UUJN has mentioned aboutCyber Notary. This study uses a normative approach, which includes conceptual and legislative approaches. The urgency of implementing the conceptCyber Notaryin the digital era andSociety5.0 in Indonesia needs to be applied immediately. Following the global development of the ASEAN Economic Community, as well as the obligations as a memberUINL since the Indonesian Notary Association (INI) officially joined as the 66th UINL member on May 30, 1997 in Santo Domingo, Dominica. So the author sees that it is very urgent for the Implementation of Cyber Notary to be implemented in Indonesia to support the goals of the MEA and Embody the UINL Conventions as a country with a Civil Law system. In conclusion, Indonesia must follow the development of the Cyber Notary concept from countries bound by UINL so that Indonesia is not left behind in world developments.